Trampoline reflex. Neurophysiological and experimental model - S. V. Muravyov; Yu. V. Karakulova; I. D. Shitoev; G. Z. Kloyan (Нервно-мышечные болезни)
Background. Prolaptology is an area dedicated to the study and correction of pelvic organ prolapse, which remains an unsolved task of gynecology at the current stage of its development. Trampoline reflex – contraction of the pelvic floor muscles in response to an increase in intra-abdominal pressure in the “hammock mode/trampoline”. It is shown that the entire thickness of the pelvic floor muscles implements the trampoline reflex as a form of “fast” phasic reflex, and the background tone of the pelvic floor muscles is determined by “slow” tonic reflexes.Aim. To study the structural and functional organization of the trampoline reflex, to propose an experimental neurophysiological model of its objectification.Materials and methods. Data from open literature sources were used to build a theoretical neurophysiological model. An experimental neurophysiological model was built on the basis of a study of three healthy female volunteers over the age of 18 (average age is 30.00 ± 2.66 years). Registration of the trampoline reflex was carried out using an individual vaginal electrode (2nd channel of abduction) with unilateral stimulation of the diaphragmatic nerve and withdrawal of motor responses from the diaphragm (1st channel of abduction).Results. It is shown that the amplitude characteristics of the motor responses of the diaphragm of adult female subjects are significantly lower than those described earlier, and the motor response of the vaginal muscles during stimulation of the diaphragmatic nerve has a low amplitude, the principal possibility of its registration is associated with traumatic events from the bottom. The inversion of the motor response of the vaginal muscles is associated with the technical features of its registration.Conclusion. A neurophysiological model and a method for registering the reflex activity of the pelvic floor muscles are presented, which allows expanding the possibilities of diagnosing pelvic organ dysfunction from the position of impaired innervation of motor innervation and «imperfections» of the pelvic floor as an efferent link of the trampoline reflex.